Perlindungan Hukum Peserta BPJS Atas Tindakan Penolakan Rumah Sakit - Sulaiman Sulaiman; Emy Rosnawati (Indonesian Journal of Law and Economics Review, 2017)
BPJS health is a government program to guarantee the health of the people. In fact there are still health-care providers who do not perform their functions properly because they refuse patients participating BPJS health. This study aims to determine the legal protection for patients participating BJPS health and find out whether the hospital in bekasi violate. This research uses normative method with approach of regulation of law. Patient's legal protection of health BPJS that is rejected by the hospital ie the patient can sue through general court or special authorized institution. The rejection of the patient by the hospital home is the responsibility of BPJS Health and the hospital is responsible for the negligence of his medical personnel. This research is useful for writers and readers to increase knowledge about legal protection of BPJS participants' patients, for legal practitioner is expected to give input about solving problem of patient protection of patient health BPJS for hospital rejection to give health service.